2022
DOI: 10.1021/acsomega.2c00948
|View full text |Cite
|
Sign up to set email alerts
|

Water/InP(001) from Density Functional Theory

Abstract: The interface between water and the In-rich InP(001) surface is studied by density functional theory with water coverage ranging from single molecules to multiple overlayers. Single molecules attach preferably to three-fold coordinated surface In atoms. Water dissociation is energetically favorable but hindered by an energy barrier that decreases with increasing water coverage. There is an attractive interaction between InP adsorbed water molecules that leads to the formation of molecular clusters and complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…This also confirms that the P dangling bond center itself is not the active site for water dissociation because beyond the H vacancy as a stable OH site, a neighboring active site for the remaining H adsorption as a further product of H 2 O dissociation is missing. Furthermore, recent studies on In-rich InP (001) suggest that free In sites are required for the dissociation of molecular water on InP surfaces . For that reason, we suggest that water dissociation only occurs at step edges rather than on terraces of the P-rich InP (001) surface.…”
Section: Water Adsorptionmentioning
confidence: 53%
“…This also confirms that the P dangling bond center itself is not the active site for water dissociation because beyond the H vacancy as a stable OH site, a neighboring active site for the remaining H adsorption as a further product of H 2 O dissociation is missing. Furthermore, recent studies on In-rich InP (001) suggest that free In sites are required for the dissociation of molecular water on InP surfaces . For that reason, we suggest that water dissociation only occurs at step edges rather than on terraces of the P-rich InP (001) surface.…”
Section: Water Adsorptionmentioning
confidence: 53%
“…This would be compatible with the adsorption of chloride on an In-terminated surface, leading to the formation of an InCl surface film starting from −0.55 V (Ag/AgCl), 22 which would also explain the differences at lower photon energies to H 2 SO 4 . The further change of the anisotropy at cathodic potentials beyond −1.5 V could then be related to the reordering of the (near-)interface water 26 or the adsorption of protons/hydrogen on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…24 Computational studies have reported on the structure and electronic properties of the pristine and oxidised InP surface using density-functional theory as well as molecular dynamics. 18,26,27 Wood et al 18 investigated the interaction of gasphase and liquid water with the pristine and oxygen-rich surfaces. Alvarado et al 26,27 changed water coverage adsorbed on InP from single molecules to water lm, and they found the OER and HER energetics to be modied due to the adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…InP coated with Pt possesses photovoltage of 0.63 V for HER. , The calculated overpotential of InP for HER by density functional theory is 0.2–0.3 V, while we are not aware of the literature data on the measured overpotential. Tafel slopes 120 and 310 mV/dec were observed for HER on the illuminated p-InP in 1 M H 2 SO 4 solution, Figure .…”
Section: Introductionmentioning
confidence: 91%